YOUTH CRIME INVESTIGATION AS AN OBJECT OF CRIMINALISTIC RESEARCH - KARAGODIN Valeriy Nikolaevich (Правовое государство: теория и практика, 2024)
The purposes of the study is to analyze crimes committed by young people; to identify the signs that distinguish the acts of these persons from the assaults of others; to consider the possibilities and directions for developing practical recommendations for the investigation of criminal cases against young people. An optional purpose is to determine the criminalistic significance of the provisions on the investigation of youth crimes and the need to form a privatescientific theory on their basis. The relevance of the study is defined by the social significance of youth crime investigation activities. Timely suppression of this type of crime allows, if not completely eliminating, then significantly weakening the negative impact of young members of the criminogenic contingent on the law-abiding population, including young people. Criminal activities of this type often create obstacles to the development of socially-oriented youth. Therefore, timely detection of the crimes of the analyzed group to some extent allows to create more favorable conditions for the development of young people not involved in criminal activities. The relevance is also determined by the lack of research into the criminal and post-criminal behavior of young people over the age of 18. The methods of scientific knowledge used in this study comprise analysis, synthesis, comparison, hypothesis, modelling, extrapolation. The results of the study include the conclusion about the creation of systematized, logically connected, scientifically substantiated provisions on the specifics of juvenile criminal and post-criminal behavior, which determine the specifics of criminal investigations involving persons of this age group. These and other attributes of the analyzed provisions allow to characterize them as a private criminalistic doctrine. At the same time, more research is required to develop a broader criminalistic doctrine of youth crime investigation. When conducting research in this direction, it is necessary to identify specific patterns of committing and investigating crimes of this type. Some of them are already identified and mentioned in this article, but they need more serious explanation and systematization. In the light of the conducted research, the concept that is the theoretical basis of the doctrine of juvenile crime investigation can be significantly adjusted.